A spatiotemporal assessment of field residues of rice, maize, and wheat at provincial and county levels in China. Issue 10 (15th May 2019) - Lin, Tao; Xu, Jialu; Shen, Xiqiang; Jiang, Hao; Zhong, Renhai; Wu, Sensen; Du, Zhenhong; Rodriguez, Luis; Ting, K. C.
Abstract: China has a huge resource potential for biomass‐based renewable energy development, but the resources of field residues are still not effectively used. Rice, maize, and wheat made up 89% of staple crop production in China in 2009. A comprehensive assessment of field residues of these three crops is necessary for the development of biomass‐based industries. This research was based on multiyear county‐level data of crop production, area and yield, as well as the crop phenology information from agrometeorological stations. Spatial and temporal analyses were conducted to quantify the spatial patterns, seasonal variations, and temporal trends of the three major field residues. The mean amount of field residue of rice, maize, and wheat was 470.8 Mt/year from 2002 to 2009. Rice residue topped the field residues at 188.5 Mt/year, followed by maize (152.6 Mt/year) and wheat (129.8 Mt/year). The resource supply of field residues varied temporally throughout the season, where peak months are May, June, September, and October. The resources of all three field residues increased from 2002 to 2009, topped by maize residues at a rate of 10.0 Mt/year. Spatially, high production counties had the fast growth rate and a strong positive spatial autocorrelation. The results showed that the intersection area of East and South Central regions has a spatially concentrated residue density and a stable supply for 5 months. The region can be considered as a suitable region for bioenergy development. A better understanding of spatial and temporal distribution of crop residues could facilitate strategic and tactical bioenergy planning. Abstract : China has a huge resource potential for bioenergy, but the biomass resources are not yet efficiently used for industrialization. We conducted spatiotemporal analyses to quantify the distributions of field residues from rice, maize, and wheat, based on multiyear county‐level data. The field residues increased from 2002 to 2009. Temporally, biomass supply peaked in May, June, September, and October. Spatially, high production counties had fast growth rates and a strong positive spatial autocorrelation. The intersection of East and South Central regions is suggested for developing bioenergy. A better understanding of residue distribution could facilitate strategic and tactical bioenergy planning.